RETURN SAHAM MEMODERASI HUBUNGAN GOOD CORPORATE GOVERNANCE MECHANISM DAN NILAI PERUSAHAAN - Dhea Ramana Putri (2021)
The purpose of this study is to examine the influence of good corporate governance (GCG) mechanism on firm value with stock returns as moderating variable and firm size as control variable. Firm value measured by Tobin's Q. GCG mechanism measured by independent board of commissioners, board of directors, audit committee, institutional ownership and managerial ownership. Capital Asset Pricing Model (CAPM) as measurement of stock returns and company size measured by total asset. The population in this study is the property and real estate companies listed on the Indonesia Stock Exchange for the period of 2015-2019. The sample collected on this study is 85 samples using purposive sampling method. Hypothesis testing used Multiple Linear Regression Analysis with STATA version 16. This study shows that 1) board of directors and audit committee have a significant positive influence on firm value; 2) independent board of commissioners, institutional ownership, and managerial ownership have no influence on firm value; and 3) stock returns cannot moderate the relationship between independent of board commissioners, board of directors, audit committee, institutional ownership and managerial ownership on firm value.